2017
DOI: 10.1371/journal.pgen.1007092
|View full text |Cite
|
Sign up to set email alerts
|

Flip/flop mating-type switching in the methylotrophic yeast Ogataea polymorpha is regulated by an Efg1-Rme1-Ste12 pathway

Abstract: In haploid cells of Ogataea (Hansenula) polymorpha an environmental signal, nitrogen starvation, induces a reversible change in the structure of a chromosome. This process, mating-type switching, inverts a 19-kb DNA region to place either MATa or MATα genes under centromeric repression of transcription, depending on the orientation of the region. Here, we investigated the genetic pathway that controls switching. We characterized the transcriptomes of haploid and diploid O. polymorpha by RNAseq in rich and nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 73 publications
0
20
0
Order By: Relevance
“…Notably, Rme1 appears to play roles in various aspects of yeast sexuality although in a manner that varies from species to species. In Kluyveromyces lactis , Rme1 acts as a positive regulator of mating-type switching and expression of haploid-specific genes integrating starvation signals 49 while in Ogataea polymorpha , Rme1 positively regulates nitrogen-starvation-dependent mating-type switching and mating 50 . Our observation provides yet another function for Rme1, with a role in the formation of asexual chlamydospores, highlighting multiple events of functional rewiring during the evolution of the Saccharomycotina .…”
Section: Discussionmentioning
confidence: 99%
“…Notably, Rme1 appears to play roles in various aspects of yeast sexuality although in a manner that varies from species to species. In Kluyveromyces lactis , Rme1 acts as a positive regulator of mating-type switching and expression of haploid-specific genes integrating starvation signals 49 while in Ogataea polymorpha , Rme1 positively regulates nitrogen-starvation-dependent mating-type switching and mating 50 . Our observation provides yet another function for Rme1, with a role in the formation of asexual chlamydospores, highlighting multiple events of functional rewiring during the evolution of the Saccharomycotina .…”
Section: Discussionmentioning
confidence: 99%
“…4F). Such short telomeric DNA fragments were observed in other yeast strains with increased telomere recombination 41,53 . Indeed, we found that disruption of the telomerase RNA gene (HpTER) in the B 1–526 strain neither changed telomere length nor induced senescence at any time point analyzed (Fig.…”
Section: Resultsmentioning
confidence: 68%
“…Since this analysis is not feasible in H . polymorpha DL-1 (due to its semi-sterility) 53 , we used its closest sibling H . polymorpha CBS4732 (a.k.a.…”
Section: Resultsmentioning
confidence: 99%
“…Although these genes are expressed under rich media conditions, they are strongly induced in K. phaffii upon transfer of the cells to starvation conditions and in response to pheromone (Heistinger et al, ). In O. polymorpha , the pheromone receptors and other mating pathway genes are induced by activation of STE12 , which occurs in response to a nitrogen starvation signal (Hanson, Byrne, & Wolfe, ). These findings suggest that the low levels of expression of mating pathway genes in rich media is not sufficient to induce a response.…”
Section: Discussionmentioning
confidence: 99%